2020
DOI: 10.1142/s0218301320500718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pairing phase transition in Sn-isotopes within semiclassical approach

Abstract: We demonstrate that pairing phase transition (superfluid to normal) can be described quite generally in terms of the thermodynamical properties after verifying the obtained level densities with the available experimental data for [Formula: see text]- isotopes. Periodic-orbit theory conveniently connects the oscillatory part of level density to the underlying classical periodic orbits and hence, leads to the shell effects in the single-particle level density. Such methods incorporated with pairing effects can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…'s and hence, the disintegration energies to calculate α-decay half-lives. Being non perturbative in nature, these techniques have been employed many times in the past to understand various aspects of nuclear structure viz shell evolution [30,70,75,[88][89][90][91][92][93][94][95][96][97]. From our analysis, we have found that FRDM and our semiclassical method produce disintegration energies of same order.…”
Section: Identification Bymentioning
confidence: 79%
“…'s and hence, the disintegration energies to calculate α-decay half-lives. Being non perturbative in nature, these techniques have been employed many times in the past to understand various aspects of nuclear structure viz shell evolution [30,70,75,[88][89][90][91][92][93][94][95][96][97]. From our analysis, we have found that FRDM and our semiclassical method produce disintegration energies of same order.…”
Section: Identification Bymentioning
confidence: 79%
“…Semiclassical methods have been extensively used in the past to describe various physical phenomena because of their non-perturbative nature [46][47][48][49][50][51][52][53][54][55][56][57][58][59]. We have determined the α-decay half-lives of even-even SHN whose atomic numbers lie in 118 Z 126 regime employing interaction potential involving Coulomb and proximity potentials using semiclassically obtained Q α -values as an input [60].…”
Section: Introductionmentioning
confidence: 99%